DAMPAK INOVASI DIGITAL TERHADAP KEWIRAUSAHAAN : SYSTEM LITERATUR REVIEW (SLR) - Nabila, Tuti; Veri, Jhon (JURNAL ILMU MANAJEMEN DAN KEWIRAUSAHAAN (JIMK), 2024)
Competitiveness by helping entrepreneurs optimize operational efficiency, expand market reach, and create products that better meet consumer needs. Furthermore, entrepreneurs’ ability to integrate this technology significantly supports the improvement of business performance, both in terms of productivity and long-term sustainability. This study uses the Systematic Literature Review (SLR) method, collecting and filtering relevant articles through Google Scholar. Of the approximately 40,000 articles found, 35 were considered relevant, and after further filtering, only 6 articles met the quality standards for in-depth analysis. The study also emphasizes that the long-term success of a business depends not only on digital innovation but also on the entrepreneurial skills and business experience of the entrepreneur. By combining digital innovation with strong entrepreneurial skills, businesses can grow faster, create new jobs, and improve product quality and market competitiveness. These findings offer valuable insights for entrepreneurs who want to thrive in the ever-evolving digital era